The Islamic world-system : a study in polity-market interaction - Choudhury, Masudul Alam (London ; New York : RoutledgeCurzon, 2004)
This book presents an alternative vision of globalization and explores the epistemology from the quran and the prophetic guidance sunnah, that underpins the systemic unity at the heart of the islamic concept of world-system.
"Transferred to digital printing 2006"--T.p. verso.
Includes bibliographical references and index.
mf 12/11/2018
Loans
Keywords: Economics---Religious aspects--Islam; Globalization---Religious aspects--Islam; Islam and the social sciences; Islam--Doctrines